Restructuring of Non-Performing Loans as a Legal Protection Measure for Debtors - Tata Cendekia Putra Sinaga; Mhd Yadi Harahap (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
This study aims to determine the form of legal protection for customers indicated to have non-performing loans at PT. Bank Sumut Medan, Polonia Branch, based on Bank Indonesia Regulation Number 14/15/PBI/2021. To address this issue, the researcher employs a normative juridical research type with a case study approach and a statutory approach. The data used consists of both secondary and primary data. The data collection techniques include interviews aimed at obtaining data on the resolution of problematic loans through restructuring at PT. Bank Sumut Medan, Polonia Branch, as well as questionnaires for respondents and employees. Additionally, the secondary data in this study consists of legal materials that use books or specific regulations as literature sources. The research results show that the form of legal protection for debtors in non-performing loans can be carried out through restructuring. However, it can be concluded that the loan procedures and requirements applied by Bank Sumut to its customers are already well-structured, and the loans provided are based on a well-utilized percentage of funds. Although the credit regulations implemented by Bank Sumut vary, the rate of non-performing loans remains relatively low. Keywords: Legal Protection, Debtor, Non-Performing Loan, Banking